Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Match each transformation of function [tex]\( f \)[/tex] to a feature of the transformed function.

[tex]\[
\begin{array}{ll}
\text{Feature} & \text{Transformed Function} \\
\hline
\text{y-intercept at } (0,2) & h(x) = f(x) + 2 \\
\text{asymptote of } y = 2 & h(x) = f(x) + 2 \\
\text{y-intercept at } (0,4) & g(x) = 2f(x) \\
\text{function decreases as } x \text{ increases} & m(x) = -f(x) \\
\end{array}
\][/tex]

[tex]\[
\begin{array}{ll}
j(x) = f(x+2) & \\
g(x) = 2f(x) & \\
h(x) = f(x) + 2 & \\
m(x) = -f(x) & \\
\end{array}
\][/tex]


Sagot :

Sure, let's match each transformation of function [tex]\( f \)[/tex] to its relevant feature step-by-step.

1. Feature: [tex]\( y \)[/tex]-intercept at [tex]\((0, 2)\)[/tex]

- We need to find the function for which the [tex]\( y \)[/tex]-intercept is at the point [tex]\((0, 2)\)[/tex].
- The [tex]\( y \)[/tex]-intercept is found by evaluating the function at [tex]\( x = 0 \)[/tex].
- Given the function [tex]\( h(x) = f(x) + 2 \)[/tex], when [tex]\( x = 0 \)[/tex],
[tex]\[ h(0) = f(0) + 2 \][/tex]
If [tex]\( f(0) = 0 \)[/tex], then [tex]\( h(0) = 2 \)[/tex]. Thus, [tex]\( h(x) = f(x) + 2 \)[/tex] shifts the original function [tex]\( f \)[/tex] vertically up by 2 units, making the [tex]\( y \)[/tex]-intercept [tex]\( (0, 2) \)[/tex].

Therefore, [tex]\( h(x) = f(x) + 2 \)[/tex] corresponds to a [tex]\( y \)[/tex]-intercept at [tex]\((0, 2)\)[/tex].

2. Feature: Asymptote of [tex]\( y = 2 \)[/tex]

- An asymptote is a line that a function approaches as [tex]\( x \)[/tex] tends to infinity or negative infinity.
- For the function [tex]\( h(x) = f(x) + 2 \)[/tex], if [tex]\( f(x) \)[/tex] has a horizontal asymptote at [tex]\( y = 0 \)[/tex], then [tex]\( h(x) \)[/tex] will have a horizontal asymptote at [tex]\( y = 2 \)[/tex].
- The function [tex]\( h(x) = f(x) + 2 \)[/tex] shifts the original graph of [tex]\( f(x) \)[/tex] vertically upwards by 2 units.

Thus, [tex]\( h(x) = f(x) + 2 \)[/tex] also corresponds to an asymptote of [tex]\( y = 2 \)[/tex].

3. Feature: [tex]\( y \)[/tex]-intercept at [tex]\((0, 4)\)[/tex]

- We need to find the function for which the [tex]\( y \)[/tex]-intercept is at the point [tex]\((0, 4)\)[/tex].
- For the function [tex]\( g(x) = 2f(x) \)[/tex], evaluate it at [tex]\( x = 0 \)[/tex],
[tex]\[ g(0) = 2f(0) \][/tex]
If [tex]\( f(0) = 2 \)[/tex], then [tex]\( g(0) = 4 \)[/tex]. Thus, [tex]\( g(x) = 2f(x) \)[/tex] scales the output of the function [tex]\( f \)[/tex] by a factor of 2, making the [tex]\( y \)[/tex]-intercept [tex]\( (0, 4) \)[/tex].

Therefore, [tex]\( g(x) = 2f(x) \)[/tex] corresponds to a [tex]\( y \)[/tex]-intercept at [tex]\((0, 4)\)[/tex].

4. Feature: Function decreases as [tex]\( x \)[/tex] increases

- We need to identify the function that results in the original function [tex]\( f(x) \)[/tex] decreasing as [tex]\( x \)[/tex] increases.
- For the function [tex]\( m(x) = -f(x) \)[/tex], if [tex]\( f(x) \)[/tex] is increasing, [tex]\( -f(x) \)[/tex] will be decreasing, because negating the function inverses its slope.
[tex]\[ \text{If } f(x) \text{ increases with respect to } x, \text{then } -f(x) \text{ decreases with respect to } x. \][/tex]

Therefore, [tex]\( m(x) = -f(x) \)[/tex] corresponds to the feature where the function decreases as [tex]\( x \)[/tex] increases.

Summarizing:

- [tex]\( y \)[/tex]-intercept at [tex]\((0, 2)\)[/tex] matches with [tex]\( h(x) = f(x) + 2 \)[/tex]
- Asymptote of [tex]\( y = 2 \)[/tex] matches with [tex]\( h(x) = f(x) + 2 \)[/tex]
- [tex]\( y \)[/tex]-intercept at [tex]\((0, 4)\)[/tex] matches with [tex]\( g(x) = 2f(x) \)[/tex]
- Function decreases as [tex]\( x \)[/tex] increases matches with [tex]\( m(x) = -f(x) \)[/tex]